Long Noncoding RNA Metastasis-Associated Lung Adenocarcinoma Transcript 1 in Extracellular Vesicles Promotes Hepatic Stellate Cell Activation, Liver Fibrosis and β-Catenin Signaling Pathway - Wang, Tianqi; Zhang, Chong; Meng, Xiaoming; Zhu, Benshuai; Wang, Siyu; Yuan, Wenkang; Zhang, Sumei; Xu, Jiegou; Zhang, Chao (Frontiers in Physiology, 2022)
Evidence shows that the long noncoding RNA metastasis-associated lung adenocarcinoma transcript 1 (Lnc-MALAT1) is associated with activation of hepatic stellate cells (HSCs) and liver fibrosis in animal and in vitro studies. However, its roles in human liver fibrosis and the underlying mechanism in HSC activation are not yet defined. In our current study, the expression of Lnc-MALAT1 in the fibrotic liver tissues and in the plasma extracelllar vesicles (EVs) of liver fibrosis patients was detected by FISH and qRT-PCR. The results revealed that enhanced expression of Lnc-MALAT1 was co-localized with increased expression of the fibrotic markers (collagen I and α-SMA) and the Wnt/β-catenin signaling proteins (β-catenin, cyclinD1 and c-myc) in the fibrotic liver tissues. The level of Lnc-MALAT1 in the plasma EVs isolated from 60 liver fibrosis patients was significantly increased compared with that of the 46 control patients, and area under receiver operating curve (AUROC) analysis showed that plasma EVs-Lnc-MALAT1 was a potential diagnostic marker for liver fibrosis, especially for high liver fibrosis. Plasma EVs with highly expressed Lnc-MALAT1 derived from high liver fibrosis patients up-regulated the expression of the fibrotic markers and enhanced the Wnt/β-catenin signaling in human hepatic stellate cells LX-2, and the fibrogenic effects in LX-2 were inhibited by Lnc-MALAT1 knock-down. Interestingly, TGF-β1, a potent pro-fibrotic cytokine, promoted the expression of Lnc-MALAT1 in LX-2 and its pro-fibrotic effects were also abolished by siRNA for Lnc-MALAT1, suggesting that Lnc-MALAT1 probably functions as a common mediator in the activation and fibrogenesis of HSCs. Our results indicate that enhanced expression of Lnc-MALAT1 in the fibrotic liver stimulate the activation of HSCs and thus promote their fibrogenic activity. These results also provide evidences that Lnc-MALAT1 is a potential therapeutic target and plasma EVs-Lnc-MALAT1 is a potential diagnostic biomarker for liver fibrosis.